Entrepreneurship and the Business Cycle - Koellinger, Philipp D.; Roy Thurik, A. (The Review of Economics and Statistics, 2012)
We find new empirical regularities in the business cycle in a cross-country panel of 22 OECD countries for the period 1972 to 2007; entrepreneurship Granger-causes the cycles of the world economy. Furthermore, the entrepreneurial cycle is positively affected by the national unemployment cycle. We discuss possible causes and implications of these findings.